PENGEMBANGAN KURIKULUM BERBASIS MUATAN LOKAL DAN IMPLEMENTASINYA DI SMPN 4 DAN MTS MANGKU ALAM KONGBENG: DEVELOPMENT OF LOCAL CONTENT-BASED CURRICULUM AND ITS IMPLEMENTATION AT SMPN 4 AND MTS MANGKU ALAM KONGBENG (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This research focuses on discussing the development of a local content-based curriculum and how to plan, implement and evaluate the development of a local content-based curriculum at SMPN 4 Kongbeng and at MTs Mangku Alam Kongbeng. This research uses qualitative methods and descriptive analysis. The results of this research show that curriculum development planning at SMPN 4 and MTs Mangku Alam Kongbeng is implemented by identifying regional conditions and needs, determining the role and composition of local content, identifying local content study materials, determining local content topics or subjects, then developing competency standards, basic competencies as well as syllabus and RPP. The implementation of the curriculum is implemented by creating local BTQ program content and agricultural practices. Then, the curriculum development is evaluated using a formative evaluation model and a summative evaluation model.